2016
DOI: 10.1103/physrevc.94.054907
|View full text |Cite
|
Sign up to set email alerts
|

Λ polarization in peripheral collisions at moderately relativistic energies

Abstract: The polarization of hyperons from relativistic flow vorticity is studied in peripheral heavy ion reactions at FAIR and NICA energies, just above the threshold of the transition to the quark-gluon plasma. Previous calculations at higher energies with larger initial angular momentum, predicted significant polarization based on the classical vorticity term in the polarization, while relativistic modifications decreased the polarization and changed its structure in the momentum space. At the lower energies studied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 43 publications
3
44
2
Order By: Relevance
“…Such effects have been included in many studies based on the hydrodynamical model [1][2][3][10][11][12][13][14][15][16][17][18][19][20], and some of these studies can indeed quantitatively reproduce the polarization of Λ hyperons measured by the STAR Collaboration [21]. Studies based on the fluid dynamical approach [12] and the transport model [22] also give results that agree with the experimental observation.…”
Section: Introductionsupporting
confidence: 73%
“…Such effects have been included in many studies based on the hydrodynamical model [1][2][3][10][11][12][13][14][15][16][17][18][19][20], and some of these studies can indeed quantitatively reproduce the polarization of Λ hyperons measured by the STAR Collaboration [21]. Studies based on the fluid dynamical approach [12] and the transport model [22] also give results that agree with the experimental observation.…”
Section: Introductionsupporting
confidence: 73%
“…These new measurements indicated that the vorticity field, if assumed to be responsible for the detailed structure in the Λ polarization, may have a very nontrivial local structure in the fireball. Indeed, it has been proposed from model simulations that the vorticity can be generated from different sources, leading to a novel local vortical structure and local polarization [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The total Λ polarization is the superposition of them.…”
Section: Introductionmentioning
confidence: 99%
“…frame, and one can Lorentz boost it into 's rest frame by the following formula: The three components of the polarization 3-vectors, 2 (p x ,p y ) [or 2 0 (p x ,p y )], have different significance. As we pointed out in our earlier paper [19], the x and y components of polarization, 2 x and 2 x , in transverse momentum space [p x ,p y ] are rather trivial and form a symmetric dipole structure, which results in vanishing global polarization along the x and y direction in the participant c.m. frame.…”
mentioning
confidence: 99%
“…Afterwards, more experimental research was launched continuously, including nucleon collisions and heavy ion collisions [3][4][5][6][7][8][9]. Theoretical studies have also been under way synchronously with the experiments [10][11][12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation